Partner Reading; Pumping up the Students’ Reading Comprehension? - Sumarsono, Dedi; Hanan, Ahmad; Bagis, Abdul Kadir; P.P, Ayumaryani (JOLLT Journal of Languages and Language Teaching, 2020)
Partner Reading is a cooperative learning strategy in which two students work together to read an assigned text. This leads the students to feel free to express their prior knowledge during the discussion with their pair. This study examined the effect of Partner Reading on students' reading comprehension. This research was an experimental study with one group pre-test and post-test design. The research was conducted at one of MTs in West Lombok. The independent variable of this research was a teaching strategy that is partner reading. Students' reading comprehension was considered as a dependent variable. This research used all of the population as the sample. The research was analyzed through a t-test with SPSS 21 software. The research reveals that teaching strategies used after treatment affect significantly on the students' reading comprehension as the sig- 2 tailed shows that it was less than 0.000 at the level of significance 0.05 and N=24. It can be concluded that partner reading affects students' reading comprehension.